Species-specific variation in nesting and postfledging resource selection for two forest breeding migrant songbirds. - Julianna M A Jenkins; Frank R Thompson; John Faaborg (PLoS ONE)
Habitat selection is a fundamental component of community ecology, population ecology, and evolutionary biology and can be especially important to species with complex annual habitat requirements, such as migratory birds. Resource preferences on the breeding grounds may change during the postfledging period for migrant songbirds, however, the degree to which selection changes, timing of change, and whether all or only a few species alter their resource use is unclear. We compared resource selection for nest sites and resource selection by postfledging juvenile ovenbirds (Seiurus aurocapilla) and Acadian flycatchers (Empidonax virescens) followed with radio telemetry in Missouri mature forest fragments from 2012-2015. We used Bayesian discrete choice modeling to evaluate support for local vegetation characteristics on the probability of selection for nest sites and locations utilized by different ages of postfledging juveniles. Patterns of resource selection variation were species-specific. Resource selection models indicated that Acadian flycatcher habitat selection criteria were similar for nesting and dependent postfledging juveniles and selection criteria diverged when juveniles became independent from adults. After independence, flycatcher resource selection was more associated with understory foliage density. Ovenbirds differed in selection criteria between the nesting and postfledging periods. Fledgling ovenbirds selected areas with higher densities of understory structure compared to nest sites, and the effect of foliage density on selection increased as juveniles aged and gained independence. The differences observed between two sympatric forest nesting species, in both the timing and degree of change in resource selection criteria over the course of the breeding season, illustrates the importance of considering species-specific traits and postfledging requirements when developing conservation efforts, especially when foraging guilds or prey bases differ. We recommend that postfledging habitat selection be considered in future conservation efforts dealing with Neotropical migrants and other forest breeding songbirds.